Follicular lymphoma transforming to DLBCL and reverting back to follicular lymphoma at relapse—a case report - M. C. Suresh Babu; Antony George Francis Thottian; D. Lokanatha; Linu Abraham Jacob; K. N. Lokesh; A. H. Rudresha; L. K. Rajeev; Saldanha Smitha; Syed Adil Hassan; Khandare Pravin Ashok; C. S. Premalatha; M. N. Suma (Journal of the Egyptian National Cancer Institute, 2020)
Abstract Background Transformation of low-grade follicular lymphoma to high-grade diffuse large B cell lymphoma (DLBCL) is known. However, the opposite is not commonly reported. In this report, we present a case of follicular lymphoma that underwent transformation to DLBCL. Three years after treatment for histologic transformation, the patient presented again with low-grade follicular lymphoma at the same site which is unusual in the natural history of follicular lymphoma. Case presentation A 50-year-old female patient presented to us with complaints of slowly progressing swelling in the neck on the left side for a duration of 1 year. Past history of the patient revealed a diagnosis of follicular lymphoma in 2004 for which the patient had taken prednisolone and chlorambucil. Details of staging were not available with the patient. After a complete work-up, she was diagnosed as DLBCL, stage IIIE. She was treated with 6 cycles of CHOP regimen. She had very good response to chemotherapy. However, she defaulted and was lost to follow-up. She presented again after 3 years with history of painless progressive swelling in the right side of the neck for the last 1 year. Examination revealed cervical lymph nodes and ascites. This time, a repeat biopsy and immunohistochemistry was suggestive of follicular lymphoma. In view of significant ascites, she was started on chemotherapy with CVP regimen. After 6 cycles, she has good partial response and resolution of ascites. She is currently on follow-up. Conclusions We have presented a case of FL that has transformed to DLBCL after 10 years of diagnosis. After HT, she was treated with CHOP chemotherapy and the patient relapsed again after 3 years with follicular lymphoma histology. This case highlights the unique and varied natural history of follicular lymphoma that may be attributed to different subclones of malignant cells that may have arisen from a common progenitor FL cell and differential effect of chemotherapy on these subclones.